Effect of an integrated neonatal care kit on neonatal health outcomes: a cluster randomised controlled trial in rural Pakistan. Issue 3 (16th May 2019) - Pell, Lisa G; Turab, Ali; Bassani, Diego G; Shi, Joy; Soofi, Sajid; Hussain, Masawar; Ariff, Shabina; Bhutta, Zulfiqar A; Morris, Shaun K
Abstract : Introduction: In 2016, 2.6 million children died during their first month of life. We assessed the effectiveness of an integrated neonatal care kit (iNCK) on neonatal survival and other health outcomes in rural Pakistan. Methods: We conducted a community-based, cluster randomised, pragmatic, open-label, controlled intervention trial in Rahim Yar Khan, Punjab, Pakistan. Clusters, 150 villages and their lady health workers (LHWs), were randomly assigned to deliver the iNCK (intervention) or standard of care (control). In intervention clusters, LHWs delivered the iNCK and education on its use to pregnant women. The iNCK contained a clean birth kit, chlorhexidine, sunflower oil, a continuous temperature monitor (ThermoSpot), a heat reflective blanket and reusable heat pack. LHWs were also given a hand-held scale. The iNCK was implemented primarily by caregivers. The primary outcome was all-cause neonatal mortality. Outcomes are reported at the individual level, adjusted for cluster allocation. Enrolment took place between April 2014 and July 2015 and participant follow-up concluded in August 2015. Results: 5451 pregnant women (2663 and 2788 in intervention and control arms, respectively) and their 5286 liveborn newborns (2585 and 2701 in intervention and control arms, respectively) were enrolled. 147 newborn deaths were reported, 65 in the intervention arm (25.4 per 1000 live births) compared with 82 in the control arm (30.6 per 1000 live births). Neonatal mortality was not significantly different between treatment groups (risk ratio 0.83, 95% CI 0.58 – 1.18; p = 0.30). Conclusion: Providing co-packaged interventions directly to women did not significantly reduce neonatal mortality. Further research is needed to improve compliance with intended iNCK use.